Functional Outcome and Quality of Life After Nonoperative Treatment of Posterior Process Fractures of the Talus. (December 2019) - Wijers, Olivier; Engelmann, Esmee W.M.; Posthuma, Jelle J.; Halm, Jens A.; Schepers, Tim
Background: Fractures of the posterior process of the talus are frequently overlooked, possibly leading to nonunion, arthritis, and chronic pain. Given the rare occurrence, previous case series have been small and without functional outcome scores. Therefore, we aimed to provide evidence on outcomes after nonoperative and operative management of posterior process fractures of the talus. Methods: All patients treated at a level 1 trauma center between 2012 and 2018 were retrospectively evaluated. Patient, fracture, and treatment characteristics were collected, and functional outcome as well as quality of life were assessed. Twenty-nine patients with posterior process fractures of the talus were identified in our database. Results: The most frequently seen mechanism of trauma was fall from height in 13 patients (44.8%). Twenty-two patients underwent primary arthrodesis or operative reduction and fixation of the fracture (75.9%). Eighty-two percent of the patients returned the questionnaires with a mean follow-up of 6 years. The 2 patients with primary arthrodesis were excluded from outcome analysis. The mean Foot Function Index score was 1.8 (range 0.0-10). The mean American Orthopaedic Foot & Ankle Society (AOFAS) score was 78.7 points (range 0-100). The mean quality of life EuroQol-5D (EQ-5D) index score was 0.78 (range −0.26 to 1). The mean visual analog scale (VAS) on overall patient satisfaction was 8.2 (range 1-10). Conclusion: Operative management of extended posterior talar fractures was found to provide good functional outcome, quality of life, and patient satisfaction. Although the patients treated nonoperatively were found to have less severe injuries, they demonstrated worse overall outcome, which is supportive of surgical management. Nonoperative treatment is therefore only justified in selected patients. Level of Evidence: Level IV, retrospective case series.